Heterojunction Channels in Oxide Semiconductors for Visible‐Blind Nonvolatile Optoelectronic Memories. (8th October 2020) - Tai, Mao‐Chou; Wang, Yu‐Xuan; Chang, Ting‐Chang; Lin, Chih‐Chih; Tu, Yu‐Fa; Hung, Yang‐Hao; Ciou, Fong‐Min; Lin, Yu‐Shan; Sze, Simon
Abstract: Optoelectronic memory whose digital signals depend on electrical as well as optical sources have attracted tremendous attention recently due to their potential in applications, including optical communication systems, neural networks, and image correlation systems. In this work, metal‐oxide semiconductors for use as optical memory devices are accomplished through a heterojunction channel layer which acts as a quantum confinement architecture confining electrons to the front channel. Compared to conventional memories, which rely on electron injections that cause hot electron degradation, the proposed device is based on a floating body effect. After irradiation, photo‐excited carriers are separated under a lateral electrical field, and generated holes are left in the back channel, which facilitates data storage behavior. Beneficial characteristics include a memory window (≈4.6 V), a high on/off ratio (≈10 6 ), and low operating voltage (<20 V). Furthermore, photo‐excited carriers are only generated when irradiated by ultraviolet light, leading to a visible‐blind optical memory. A retention of more than 10 years and endurance cycle of more than 1000 cycles demonstrate its nonvolatile behaviors. This work provides a novel heterojunction channel layer architecture in disordered oxide semiconductors and provides a novel idea for a wide range of unipolar materials in future optoelectronic memory devices. Abstract : A nonvolatile optoelectronic memory by integrating heterostructures into unipolar materials is reported. A reliable memory with high on/off ratios and a low operating voltage is achieved through floating body effect. Furthermore, visible‐blind programming and multi‐bit functions are attained through the properties of the wide bandgap material, InGaZnO. The proposed work has potential to improve technical applications in memory fields.